2022
DOI: 10.1186/s13071-022-05443-z
|View full text |Cite
|
Sign up to set email alerts
|

Excretory-secretory products from the brown stomach worm, Teladorsagia circumcincta, exert antimicrobial activity in in vitro growth assays

Abstract: Background Over the past decade, evidence has emerged of the ability of gastrointestinal (GI) helminth parasites to alter the composition of the host gut microbiome; however, the mechanism(s) underpinning such interactions remain unclear. In the current study, we (i) undertake proteomic analyses of the excretory-secretory products (ESPs), including secreted extracellular vesicles (EVs), of the ‘brown stomach worm’ Teladorsagia circumcincta, one of the major agents causing parasite gastroenterit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 78 publications
(103 reference statements)
0
12
1
Order By: Relevance
“…Another interesting study carried out in the nematode Teladorsagia circumcincta combined proteomics and bioinformatics screening to detect antimicrobial ESP in secreted EVs. Although these peptides were not individually tested, the authors were able to demonstrate the antimicrobial activity carried by EVs and ESP, validating the reliability of their approach [66]. Despite these encouraging outputs, the computer-assisted identification of novel HDP in helminths will remain a challenging task for the years to come, due to the variable quality of available helminth genome assemblies, the different technical approaches used for sequencing and assembly, the inherent complexity of these genomes and the risk of exogenous contamination [67].…”
Section: Computation Approaches For the Discovery Of Novel Helminthic...mentioning
confidence: 72%
“…Another interesting study carried out in the nematode Teladorsagia circumcincta combined proteomics and bioinformatics screening to detect antimicrobial ESP in secreted EVs. Although these peptides were not individually tested, the authors were able to demonstrate the antimicrobial activity carried by EVs and ESP, validating the reliability of their approach [66]. Despite these encouraging outputs, the computer-assisted identification of novel HDP in helminths will remain a challenging task for the years to come, due to the variable quality of available helminth genome assemblies, the different technical approaches used for sequencing and assembly, the inherent complexity of these genomes and the risk of exogenous contamination [67].…”
Section: Computation Approaches For the Discovery Of Novel Helminthic...mentioning
confidence: 72%
“…Indeed, A. suum ESPs contain several antimicrobial molecules, including cecropin-P2 [25] , A. suum antibacterial factor (ASABF), lysozymes, as well as C-type lectin domain-containing proteins [5] , that can disrupt bacterial membranes to cause cell lysis, or promote lethal agglutination of bacterial cells. More recently, we also demonstrated that in vitro exposure of E. coli to ESPs from the ‘brown stomach worm’, Teladorsagia circumcincta , an abomasal parasite of small ruminants, results in significant reductions of colony forming units over a 3-h period [24] . Proteomics analyses of T. circumcincta ESPs, coupled with bioinformatics screening of amino acid sequence data, identified several putative AMPs, including a histone H4-like protein, an Ancylostoma -secreted protein (ASP)-like protein, and an invertebrate-specific lysozyme-like enzyme known as destabilase [24] .…”
Section: Introductionmentioning
confidence: 75%
“…More recently, we also demonstrated that in vitro exposure of E. coli to ESPs from the ‘brown stomach worm’, Teladorsagia circumcincta , an abomasal parasite of small ruminants, results in significant reductions of colony forming units over a 3-h period [24] . Proteomics analyses of T. circumcincta ESPs, coupled with bioinformatics screening of amino acid sequence data, identified several putative AMPs, including a histone H4-like protein, an Ancylostoma -secreted protein (ASP)-like protein, and an invertebrate-specific lysozyme-like enzyme known as destabilase [24] . Previously, we hypothesised that the antimicrobial properties of ESPs from T. circumcincta , as well as of ESPs from other GI helminths of humans and animals, may be attributed to the activity of secreted AMPs, free and/or encapsulated in secreted extracellular vesicles (EVs) [24] .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…For 2D SDS PAGE protein spots, the method of Duncan et al (2018) was utilized for LC-MSMS. For whole A. perfoliata Orbitrap Fusion™ Tribrid™ mass spectrometer (Thermo Scientific™), with EASY-Spray™ Source, coupled to an UltiMate™ 3000 RSLCnano System (Thermo Scientific™) as per methods of Rooney et al (2022).…”
Section: Trypsin Digestion and Mass Spectrometrymentioning
confidence: 99%